A and d seem correct to me.
b and c are definitely wrong.
Answer:
hi
Step-by-step explanation:
thx for the points
:)
Answer:
![\lim_{x \to 2} (x+1)(3x^2-9) = 9](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%202%7D%20%28x%2B1%29%283x%5E2-9%29%20%3D%209)
Step-by-step explanation:
Step 1: Write out limit
![\lim_{x \to 2} (x+1)(3x^2-9)](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%202%7D%20%28x%2B1%29%283x%5E2-9%29)
Step 2: Evaluate
(2 + 1)(3(2)² - 9)
3(3(4) - 9)
3(12 - 9)
3(3)
9
6[13-2(4+1)]
Solve what is in the bracket first.
Parenthesis first.
6[13-8-2]
6(3)
18
Answer:
6
Step-by-step explanation:
g(5) represents x=5
you would substitue 5 for x in g(x)=2x-4
g(5)=2(5)-4
g=6